Programa de especialistas para la Atención Primaria. Ministerio de Salud de Chile. Adherencia al programa en sus primeros cuatro años de funcionamiento - Vargas C., Nelson A.; Gómez A., Germán (Revista Hospital Clínico Universidad de Chile, 2012)
In 2008 the Chilean Ministry of Health initiated with some universities a training program for specialist in a primary care setting which has attracted attention given its novelty and new design. AIM: To measure students’ adherence to the Program at the University of Chile after four years of experience. MATERIAL AND METHOD. A life table analysis was performed with information obtained from University’s School of Medicine and Ministry of Health records. Life tables were built to measure adherence for all students as a whole and for each individual specialty: Internal Medicine, Obstetrics and Gynecology, Pediatrics and Psychiatry. RESULTS. Total number of students was 148 physicians admitted for training in the already mentioned specialties. Internal Medicine and Pediatrics gathered close to one third of admissions each. Years 2008 and 2009 had lower number of admissions. Annual rates of desertion were comparable in the first (4.4%) and third (5%) years with a minor decrease in the second (1.7%) and an increase in the fourth (4.8%) year. However, in the latter proportions became unstables due to a lower number of students. After four years program adherence reached 85% of students. Adherences after four years by specialty were: Internal Medicine: 88.7%; Obstetrics and Gynecology: 78.8%, with losses concentrated only in the first year; Pediatrics: 75.8% and Adults Psychiatry: 84.8%. DISCUSSION. Accumulated program adherence is considered satisfactory and should be compared with other training programs and other universities results. An accurate measurement of Program results should include a close surveillance of health markers of populations served by the students under training. These results and others coming from other studies make believe that this program is improving the country’s family model of care by keeping stable physicians at primary level.